Creating a Sustainably Impactful Project: Organizational Prerequisites - AKZAMBEKKYZY Akbota; DALCHER Darren; SARKAMBAYEVA Shynara; FORREST Jeffrey YI-LIN (Foundations of Management, 2025)
History suggests that some projects enjoyed lasting impacts on the development of the creators’ organization. However, no consensus exists on how an organization can create such projects to achieve desired long-term sustainable impacts. This article is devoted to a comprehensive study of ways to create a sustainably impactful project, taking as a basis the general criteria for “great projects” as successful projects in the long term. Reviewing the literature, we identify environmental factors for great projects and correlate these factors with criteria that characterize excellent organizations. The characteristics of excellent organizations known from current literature were enlarged to build a cohesive model of organization capable of creating a sustainably impactful project. Hence, we develop a conceptual model that demonstrates the process of creating sustainably impactful projects one after another. Based on the results of this study, organizations will be expected to be able to develop their roadmaps of growth with a focus on strengthening the conditions under which sustainably impactful projects can be developed for their long-term development and superior performance.